Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T16:43:34+01:00
A) ax+2ay= a(x + 2y)
b) x²y-xy²= xy(x - y)
c) x⁵+2x³= x³(x² + 2)
d)abx-aby=ab (x - y)
e)- 4aby +2abx= 2ab(-2y + x)
f) 6mn²+3mn-3m²n= 3mn(3n + 1 - m)
g) mn-m-2m²= m (n - 1 - 2m)
h) 4m +8mn-10mnp= 2m(2 + 4n - 5np)
i) x²+8x+16= x(x + 8 +16)
1 5 1
2009-11-26T16:45:11+01:00
A) ax+2ay = a(x+2y)
b) x²y-xy² = xy(x-y)
c) x⁵+2x³ = x³(x²+2)
d)abx-aby = ab(x-y)
e) - 4aby +2abx = 2ab(-2y+x)
f) 6mn²+3mn-3m²n = 3mn(2n+1-m)
g) mn-m-2m² = m(n-1-2m)
h) 4m +8mn-10mnp = 2m(2+4n-5np)
i)x²+8x+16 = (x+4)² =(x+4)(x+4)
j)81x⁴+90x²y+y² = (9x²+y)² < w tym się niestety środkowy wyraz nie zgadza:( >